(untitled) (World Economics and Finance Bulletin, 2025)
This article examines marketing research methods and their application to textile enterprises. It explores economists’ definitions and approaches to the concept of marketing research. The results of a questionnaire analysis and a SWOT analysis of a sample of textile products manufactured by Bitlis Textile LLC are presented. The potential for applying marketing research methods to textile enterprises is demonstrated, and conclusions are drawn